Electronic structure of dense amorphous carbon - Segall, Benjamin; Lee, Choon H.; Kelires, Pantelis C. (My University, 1994)
The tight-binding method is used to calculate the electronic densities of states of various models of a-C. Both models generated using Tersoff's potential and quantum mechanically derived forces show π and π* states in the σ gap in agreement with experimental data. The former models, however, have an additional large peak at the Fermi level, which is shown to derive mainly from misoriented pπ orbitals and dangling bonds. The models do not support the presence of large aromatic ring structures. We find that embedding the local π electron systems of small clusters in the rigid sp3 network leads to reduced level splittings and is thus consistent with the observed small optical gaps ≤2.5 eV.
Keywords: Electronic structure; Quantum mechanics; Carbon